Estimation of adaptable properties of winter bread wheat varieties developed by the FSBSI “ARC “Donskoy” - E. I. Nekrasov; D. M. Marchenko; M. M. Ivanisov (Зерновое хозяйство России)
An important aspect in breeding programs is to increase a potential of winter wheat productivity. At the same time, modern genotypes are required to possess not only high productivity with appropriate grain quality, but also resistance to the unfavorable effects of growing conditions. Thus, the study of the genotype according to its interaction with the environment is an integral component in the search for ways to further productivity increase of varieties. The purpose of the current study was to identify the stability and interaction of the genotype with the environment in the winter bread wheat varieties developed by the FSBSI “ARC “Donskoy”. In the study there were used 14 varieties of winter bread wheat grown after sunflower in 2018–2021. As a result of the study, there was found that the factor “year” had the greatest effect on productivity (53.72%), the factor “variety” influences on productivity on 20.17%, and the correlation of the factors “year × variety” affected on productivity on 22.40%. On average, through the years of study, the varieties’ productivity ranged from 4.81 t/ha (the variety ‘Don 107’) to 5.38 t/ha (the variety ‘Zolotoy Kolos’). The varieties ‘Lidiya’ (bi = 1.04), ‘Zhavoronok’ (bi = 1.32), ‘Kaprizulya’ (bi = 1.41), ‘Lilit’ (bi = 1.44), ‘Podarok Krymu’ (bi = 1.59) and ‘Krasa Dona’ (bi = 1.64) have shown a strong responsiveness to the changes of the environment. The varieties ‘Polina (Hom = 94.27; Cv = 8.90%) and ‘Ayuta’ (Hom = 238.85; Cv = 5.73%) were characterized by high homeostatic indices and low values of the coefficient of variance.